Anaerobic digestion of chicken manure by a leach-bed process coupled with side-stream membrane ammonia separation - ÇALLI, BARIŞ (ELSEVIER SCI LTD, 2018)
This study pioneered the use of a single-stage methanogenic leach bed reactor (LBR) for high-solids (total solid content: 14%-16%) anaerobic mono-digestion of chicken manure. Chicken manure was loaded into the LBR in cloth sachets without adding any bulking agents. Ammonia was separated and recovered by placing a hydrophobic gas diffusion membrane in a leachate collection chamber. Methane production in the membrane-integrated LBR was 0.272 m(3)/kgVS and 2.3 times higher than that in the control LBR. The results revealed that using membrane-integrated LBR for anaerobic digestion is a simple and cost-efficient technology for the monodigestion of chicken manure and ammonia removal.
Keywords: Ammonia; Mono-digestion; Membrane separation; Egg-layinghen manure; Biogas; DAIRY MANURE; BIOGAS PRODUCTION; SUBSTRATE RATIO; POULTRY LITTER; SWINE MANURE; SOLID-WASTE; INHIBITION; REMOVAL; RECOVERY; REACTORS